2021
DOI: 10.1039/d1ta02992d
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage mechanisms in vacancy-ordered Wadsley–Roth layered niobates

Abstract: Layered niobates with vacancy-ordered Wadsley–Roth structures were investigated as Li-ion battery anodes. Using operando and ex situ methods and DFT, we identify an intercalation mechanism dominated by Li-diffusion kinetics and layer evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 64 publications
(101 reference statements)
3
17
0
Order By: Relevance
“…In the past reports, low-dimensional KNb 3 O 8 materials synthesized via sol-gel or hydrothermal methods were widely applied in photocatalysis and lithium ion battery. [39][40][41][42][43] However, the disordered morphology of thick KNb 3 O 8 nanoflakes synthesized by the above methods cannot be used in micro-nano devices due to incompatibility with semiconductor processing technology. The low crystallinity, numerous oxygen defects, and unavoidable surface contamination of the liquidphase synthesized KNb 3 O 8 nanoflakes also hinder its development in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the past reports, low-dimensional KNb 3 O 8 materials synthesized via sol-gel or hydrothermal methods were widely applied in photocatalysis and lithium ion battery. [39][40][41][42][43] However, the disordered morphology of thick KNb 3 O 8 nanoflakes synthesized by the above methods cannot be used in micro-nano devices due to incompatibility with semiconductor processing technology. The low crystallinity, numerous oxygen defects, and unavoidable surface contamination of the liquidphase synthesized KNb 3 O 8 nanoflakes also hinder its development in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic shear phases, including the Wadsley–Roth structures possess crystallographic shear and have emerged as a promising and broad class of materials that display exemplary performance as electrodes. These materials are diverse in elemental constitution and block size, and even large particles of these materials are capable of impressive rates. Computational and experimental efforts have suggested that a combination of corner and edge-sharing polyhedra promote metallic conductivity and fast Li + diffusion, while suppressing large structural changes. …”
Section: Introductionmentioning
confidence: 99%
“…Shear-phase oxides contain regions of edge-sharing and corner-sharing transition metal octahedra, which promote electronic and ionic conductivity, respectively, and have emerged as promising high-rate Li + -ion battery electrode materials. Nearly all of these oxides are Nb-based, and since Nb 5+ , Nb 4+ , and Nb 3+ are all accessible oxidation states, they are capable of multielectron redox and therefore high capacities. The voltage associated with these couples (on average 1.5 V vs Li/Li + ) is suitably in the regime expected for anodes.…”
Section: Introductionmentioning
confidence: 99%